(untitled) (Desenvolvimento em Questão, 2025)
The present study sought to analyze the sustainability indicators of family livestock in the cerrado and pampa, from the perspective of livelihoods and multivariate analysis. Using the database of the Methodology for the Evaluation of Sustainable Rural Development in Family Farming (MADERUS), the Principal Component Analysis (PCA) made it possible to group the main different characteristics of family livestock into four groups. Among the main sustainability indicators, the native vegetation of the pampa biome (native field) was the main asset that differentiates the livelihoods of family farmers. The masculinization of the rural environment and the rural exodus, mainly of young people, were the main vulnerabilities assisted in the general scenario of the analysis. There are assets with satisfactory values guaranteeing sustainability to livelihoods, while others, negatively related, expose them to processes of vulnerability. Family livestock, in both biomes, creates its spaces for maneuvers, based on its means of livelihood limits and reframes responses based on its trajectories, agroecosystems and cultures. In view of this, based on the modest contribution of this research, there are two fundamental questions for future studies: i) to analyze family livestock and its typologies, including a macro system, with the aim of finding the different occurrences of vulnerabilities to the detriment of their specificities; and, ii) to evaluate in greater detail the environmental sustainability of family cattle ranchers in the cerrado.